Correlation between the cardiorespiratory endurance, dynamic postural control and thoracic kyphosis angle among the students - Farzaneh Saki; Parisa Sedaghati; Masoumeh Baghban (Fiyz̤, 2017)
Background: Any deviation in the normal spinal alignment can alter the cardiorespiratory endurance and the posture control. The aim of present study was to investigate the correlation between cardiorespiratory endurance, dynamic postural control and kyphosis angle among the students. Materials and Methods: This cross-sectional study was carried out on students (n=100; 48 girls and 52 boys) selected randomly according to inclusion criteria. Cardiorespiratory endurance, postural control and kyphosis angle were assessed using shuttle run test, Y balance test and flexible ruler, respectively. Normal distribution of the data was assessed using the Kolmogorov–Smirnov test. Data were analyzed using Pearson correlation product moment and linear regression (P≤0.05). Results: The results showed a significant negative correlation between the cardiorespiratory endurance and kyphosis angle (P=0.012, r=-0.3.3). In addition, a significant negative correlation was observed between the dynamic postural control and kyphosis angle (P=0.003, r=-0.254). Conclusion: According to our findings it seems mandatory for health and school's, sport coaches to screen the student's spinal deformities and evaluate its associated complications (e.g. decreased cardiorespiratory endurance and postural balance).